COMPARISON STUDY OF VERTICAL CYLINDER TANK DIAMETER MEASUREMENT BETWEEN STRAPPING AND OPTICAL METHOD - Firmansyah, Vera; Nugroho, Purwanto; Yienda Prihensa, Herfin; Muslim, Azis (Spektra: Jurnal Fisika dan Aplikasinya, 2020)
Vertical Cylinder Tank is used as a storage area or as a measuring tool. Liquids are used in the form of Fuel oil, Liquid Natural Gas, vegetable liquids, and other chemical liquids. The tank calibration results are in the form of a volume per height table that is used as a reference by Automatic Tank Gauging. There are two tank calibration methods, namely: the strapping method and the optical method. The process of measuring the inside or outside diameter of the tank becomes very important in the tank calibration process—the measurement of tank diameter by the strapping method using steel meters manually. At the same time, the optical method uses theodolite or total station. For tank diameters ≤ 5 m, the strapping method has smaller diameter measurement results with a difference of 0.7% compared to the optical method. In further research, a prototype can be developed that can accelerate the calibration process using the strapping method (for example, a vertical track measuring robot) or a low-cost prototype theodolite